(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
It is with great pleasure that we present to you Volume 16, Number 1, 2024, of "Voice: Biannual and Bilingual Journal” published by Autar Dei Chaudharain Research Centre (ADCRC) at Mahendra Multiple Campus, Nepalgunj, Banke, Nepal. Our journal continues to uphold its primary aim of facilitating the exchange of expertise among scholars on a global scale, fostering a dynamic platform for intellectual discourse across various disciplines. In this edition, we proudly present a multidisciplinary collection of 13 articles, with eight contributions in English and five in Nepali. This diversity reflects our commitment to linguistic inclusivity and our effort to bridge scholarly communities across different languages. The range of topics covered in this issue underscores the breadth and depth of academic inquiry being pursued by our contributors. Highlights include an in-depth analysis of the socio-economic impacts of policy changes in Nepal during the crucial decade of the 1990s, examining realism and societal dynamics in selected novels of Shashi Deshpande, and a stability evaluation of the Lanedada Twin Tunnel in KTFT, focusing on the structural stability and safety measures of a significant infrastructural project. Additionally, we have an exploration of alcohol use and its socio-economic and health effects in the Tharu community of Raptisonari Rural Municipality. There is also an analysis of historical and literary perspectives on trauma and displacement in Khushwant Singh’s "Train to Pakistan." An exploratory study on how economic changes affect consumer behavior in the jewelry market of Nepalgunj adds a practical economic perspective. A comparative study on the reading comprehension abilities of Tharu and non-Tharu students’ sheds light on educational performance influenced by cultural and linguistic factors. Finally, a contemporary assessment of Nepal’s food sovereignty status and related policies offers valuable insights into current agricultural and food security challenges. For our Nepali readers, we offer a detailed exploration of classical Sanskrit poetics and theories of rasa, along with an analysis of the purpose and cultural significance of traditional songs in the Ribdikot area. There is a historical overview and critical examination of trends in Nepali short stories, a comprehensive look at the fifth part of the Vedapurana’s gems, and an analysis of the ideologies presented in the novel "Basai."